Flour production from shrimp by‑products and sensory evaluation of flour‑based products - Fernandes, Thiago Mendes; da Silva, João Andrade; Silva, Ana Hermínia Andrade da; Cavalheiro, José Marcelino de Oliveira; Conceição, Maria Lúcia da (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the production of flour using by‑products (cephalothorax) obtained from the shrimp (Litopenaeus vannamei) industry, and to perform a sensory analysis of shrimp flour‑based products. Physicochemical and microbiological analyses on fresh cephalothorax and on manufactured flour were performed, as well as the determination of cholesterol content of this flour, and the sensorial evaluation of soup and pastry made with this flour. By the microbiological analyses, no pathogenic microorganism was detected in the samples. Physicochemical analyses of flour showed high levels of protein (50.05%) and minerals (20.97%). Shrimp cephalothorax flour showed high levels of cholesterol. The sensory evaluation indicated a good acceptance of the products, with satisfactory acceptability index (81% for soup, and 83% for pastry), which indicates that shrimp cephalothorax in the form of flour has a potential for developing new products.
Keywords: Litopenaeus vannamei; acceptance; cephalothorax; food technology